Implementation of Behavior Contract to Reduce Aggressive Behavior of Students at SMP Negeri 3 Tanete Rilau - Hadi As; Abdul Saman; Asniar Khumas (Program Studi bimbingan Konseling PPs UNM Makassar, 2020)
This study aims to investigate the degree of students’ aggressive behavior before and after being given the contract behavior treatment. This study used simple random sampling technique. The research instrument used was a Likert scale outlined in the form of a questionnaire given to the experimental group to describe students’ aggressive behavior. Descriptive statistical analysis was used to describe the aggressive behavior of students of SMP Negeri 3 in Tanete Rilau before and after the implementation of the behavior contract using frequency and percentage distribution tables. Results showed that behavior contract counseling can reduce students’ aggressive behavior. Effects of excessive aggressive behavior includes impulsive, control-lacking, agitated and easily distorted, often unable to sit still, unable to pay attention to the teacher and the task at hand, and often unable to complete homework, etc.